Assessment of the Effect of Nutrition Education Based on BASNEF Model on Decreasing Blood Lipid Profile - Soheila Samieipour; Elahe Tavassoli; Fatemeh Aliakbari; Homamodin Javadzade; Mahnoush Reisi; Fariba Fathollahi Dehkordi; Leili Rabiei (Shahrekord University of Medical Sciences, 2022)
Background and aims: Dyslipidemia is one of the major causes of cardiovascular disease (CVD); however, it can be prevented and controlled via observing and adherence to a diet. This study aimed at determining the effect of nutrition education based on BASNEF model on decreasing blood lipid profile. Methods: This clinical trial study was conducted on 150 people with a high blood lipid profile who referred to Shahrekord laboratories in 2020. The samples were randomly divided into intervention and control groups. In order to measure blood lipids such as high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), and total cholesterol (TC), 15 mL of venous blood samples were collected after 12 hours fasting before the intervention and again 2 months after the intervention. The intervention group received nutrition education based on BASNEF model, and the collected data were analyzed using SPSS version 20 software. Results: There was no significant difference between the two groups in terms of demographic variables. TG levels in the intervention group decreased significantly after the intervention (P < 0.001). In addition, TC and LDL levels decreased significantly in the intervention group after the intervention (P < 0.001), while the level of HDL index in the intervention group increased significantly after the intervention. Nonetheless, there was no significant difference in these indices in the control group after the intervention (P > 0.05). Conclusion: The significant decrease in blood lipids after a short period indicates the effect of nutrition education based on BASNEF model and adherence to proper diet on controlling blood lipids. Therefore, recommending people to adhere to a proper diet can help raise people's nutritional awareness and reduce blood lipids.